Interlayer interaction and Davydov splitting in antiferromagnetic few-layer NiPS3 - Manh Hong Nguyen; Giung Park; Je-Geun Park; Hyeonsik Cheong (npj Quantum Materials)
Abstract Interlayer interactions in few-layer NiPS3 were investigated by analyzing low-frequency interlayer vibration modes and Davydov splitting of an intralayer, A1g vibration mode at ~255 cm–1 by Raman spectroscopy as a function of temperature. The interlayer force constants were estimated from the low-frequency Raman spectra by using the linear chain model. The out-of-plane direction interlayer force constant could also be estimated separately from the Davydov splitting, which agrees well with the linear chain model analysis. The dependence of the low-frequency shear and breathing modes and the Davydov splitting on the number of layers provide a unique, reliable tool for determining the number of layers.